A new high temperature, high heating rate, low axial gradient capillary heater. (18th November 2022) - Marshall, Kenneth P.; Emerich, Hermann; McMonagle, Charles J.; Fuller, Chloe A.; Dyadkin, Vadim; Chernyshov, Dmitry; van Beek, Wouter
Abstract : A new high‐temperature capillary heater design suitable for synchrotron X‐ray diffraction, total scattering and EXAFS experiments is described. Abstract : A new heater design, capable of fast heating and cooling to and from >1000°C, has been developed at the Swiss–Norwegian Beamlines, European Synchrotron Radiation Facility, France. The design uses a SiC head to distribute heat, and resistive Si3 N4 heat cartridges to provide heat.